IDENTIFICATION OF CHARCOAL AND AMS RADIOCARBON DATING OF SAMPLES FROM THE FISH WEIR SITE (49-GUL-380) AND THE LITTLE SWEDE LITHIC SCATTER (SITE 49-XMH-1005), ALASKA - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
One partially charred wood sample from the Fish Weir site, 49-GUL-380, and two charcoal samples from the Little Swede Lithic Scatter, site 49-XMH-1005, were submitted for identification and AMS radiocarbon dating. Site 49-GUL-380 is situated near the Gulkana River in south central Alaska and is known ethnographically as the location of the northernmost fishing weir of the Gulkana-Gakona band of the Ahtna (John Jangala, personal communication, September 21, 2010). The sample was recovered from a fire-cracked rock (FCR) locus. Site 49-XMH-1005 is situated in the Tangle Lakes Archaeological District, also in south central Alaska. Charcoal samples were taken from units in a circular cluster of lithic debitage.